KESULITAN GURU BIMBINGAN DAN KONSELING DALAM MEMBERIKAN PELAYANAN BIMBINGAN DAN KONSELING DI MASA PANDEMI - Septiyana, Tiya (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2025)
The Corona Virus or Covid-19 pandemic that occurred in the world, including in Indonesia, has had a significant impact in various sectors, one of which is the education sector. With the increasing pandemic, the government has given an appeal to carry out distance learning, in order to anticipate the wider spread of the corona virus, sudden distance learning is something new for students as well as teachers, including guidance and counseling teachers. In providing guidance and counseling services to students with distance learning is a quite difficult challenge, face to face indirectly is one of the major challenge factors in the effectiveness of the provision of services provided that is optimal or not.